WHEN THE RIGHT WAS WRONGâ€: A CASE OF MISSED NEGLIGENCEâ€ - Kanchan, Tanuj; Atreya, Alok (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  We report a case where the operation site was marked wrongly on the right side of the scalp. It was the timely intervention of a member of the surgical team that the possible mishap in the form of a negligent operation on the wrong site was prevented, hence, the term missed negligence.â€ The case is reported for its significance in the field of surgery as a caution and reminder that utmost care should be taken to determine and confirm the site of the surgery. Keywords: Negligence, Res ipsa loquitur, Site, Surgery, Wrong.